Novel and Economic Approach for Synthesis of Mesoporous Silica Template and Ordered Carbon Mesoporous By Using Cation Exchange Resin - Samiee, Leila; Tasharrofi, Saeedeh; Hassani, Sedigheh S.; Fardi, Milad; Mazinani, Babak (Current Nanoscience, 2017)
Background: Porous carbon materials are promising candidate supports for various applications. Different approaches have been applied for preparation of various types of porous carbon materials which in the most of them; disordered structures as well as relatively broad pore size distribution are obtained. The most reliable method for preparing of the ordered carbon mesoporous is nano-casting using mesoporous silicas as a hard template. However one of the challenges in the nano-casting preparation is the mother silica template usually produced from expensive initial ingredients, complicated and consuming process. Therefore, in the present work, the synthesis of the ordered silica mesoporous using commercial water glass as the silica source is reported in which the silicic acid has been prepared using cation-exchange resin. Furthermore, the adsorption properties and phenolic compounds removal capability of the templated carbon mesoporous were compared with the mesoporous carbon prepared by SBA-15 and activated carbon. Method: The structural order and textural properties of the materials have been evaluated by SAXRD (Small Angle X-Ray Diffraction), SEM (Scanning Electron Microscopy), TEM (Transmission Electron Microscopy) and nitrogen adsorption–desorption analysis. Finally, the adsorption of phenolic compounds on the carbon mesoporous has been studied. Results: From SAXRD patterns it was deduced that the silicic acid amount has a considerable effect on the final order of the mesostructure. Also, the nitrogen adsorption-desorption isotherms of different silica samples represent Type IV isotherms. The formation of well-oredered hexagonal (P6mm) arrays of mesopores could be clearly observed from SEM and TEM micrographs. Moreover, the carbon templated from the optimized mesoporous silica revealed the well-ordered mesostructure along with type IV adsorption isotherm confirming the nanoporous carbon has been successfully templated. The microstructural images show the almost similar structure of the mother silica template. In addition, EDS analysis of the silica and carbon templated sample confirms the almost elimination of sodium. Finally, the performance the nanoporous carbon materials for phenolic compounds removal was investigated. It is noteworthy that the adsorption capacity and equilibrium point in the case of the prepared nanoporous carbon materials is very close to that of obtained for carbon prepared by SBA-15. Furthermore the results showed the mesoporous carbon samples exhibit considerably much higher adsorption capability in comparison to commercial activated carbon. Finally the kinetic evaluation indicates that the phenolic compounds adsorption is accordance to the pseudosecond- order kinetic model over the entire adsorption time. Conclusion: The impurity-free and well-ordered hexagonal mesoporous silica particles have been successfully synthesized by commercial water-glass using cation exchange resin. The resultant silica has high surface area (778.3 m2/g), pore volume (1.1 cm3 /g) and pore size (6.1 nm), completely comparable to mesoporous silica (SBA-15) produced by TEOS as a silica source. Moreover, the carbon nanoporous templated by the prepared mesoporous silica has a well ordered structure, high surface area (1033.9m2/g) and pore volume (1.08 cm3/g). Finally the results showed the prepared mesoporous carbon could be considered as a suitable candidate for phenolic compounds removal from water and waste water, as well. Furthermore, the experimental results also showed that the adsorption process and equilibrium data were well fitted by pseudo second-order kinetic.
Keywords: mesoporous carbon